1972
DOI: 10.1139/v72-389
|View full text |Cite
|
Sign up to set email alerts
|

Thiohydantoins. IX. Tautomerism of some Methylation Products

Abstract: The methylation product of 5,5-pentamethylene-2-thiohydantoin has been shown by U.V. and i.r. spectral studies to exist predominantly as 2-methylthio-4,4-pentamethylene-2-imidazolin-5-one in chloroform or cyclohexane, and as 2-methylthio-5,5-pentamethylene-2-imidazolin-4-one in water. The tautomerism of the methylation product of 5,5-pentamethylene-2,4-dithiohydantoin exhibits a similar sensitivity to solvent.Des etudes dans 1'u.v. et dans 1'i.r. demontrent que le produit fourni par l'action d'iodure de methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…~' ( 1 ) ~'(11) This tautomerism, defined as annular desmotropy, was studied by ir and uv spectroscopies in several hydantoin derivatives (1,2). Lempert et al (2) determined the X-ray structures of the two desmotropes of 2-S-methyl-5,5-diphenylimidazolin-4-one in 1973, and showed that the polarity of the solvent is crucial in obtaining one of the two tautomers.…”
mentioning
confidence: 99%
“…~' ( 1 ) ~'(11) This tautomerism, defined as annular desmotropy, was studied by ir and uv spectroscopies in several hydantoin derivatives (1,2). Lempert et al (2) determined the X-ray structures of the two desmotropes of 2-S-methyl-5,5-diphenylimidazolin-4-one in 1973, and showed that the polarity of the solvent is crucial in obtaining one of the two tautomers.…”
mentioning
confidence: 99%